Federico Mayor Zaragoza, recibe Premio Derechos Humanos de la Abogacía 2012 (Cultura de Paz, 2013)
DOI: http://dx.doi.org/10.5377/cultura.v18i58.1048 Cultura de Paz • Año XVIII • N° 58 • Septiembre - Diciembre 2012 P / 54